2008
DOI: 10.1007/s11524-008-9328-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence Rates among Injection Drug Users in 96 Large US Metropolitan Areas, 1992–2002

Abstract: This research presents estimates of HIV prevalence rates among injection drug users (IDUs) in large US metropolitan statistical areas (MSAs) during 1992-2002. Trend data on HIV prevalence rates in geographic areas over time are important for research on determinants of changes in HIV among IDUs. Such data also provide a foundation for the design and implementation of structural interventions for preventing the spread of HIV among IDUs. Our estimates of HIV prevalence rates among IDUs in 96 US MSAs during 1992-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
(65 reference statements)
2
40
1
Order By: Relevance
“…25 HIV-HCV co-infection was low (ranging from 30.7% to 33.3% among persons with HIV across reference methods) in this sample as compared with other PWID studies (80-89%). 7,21,22 Some of this may be attributable to age as anti-HCV is less prevalent among younger populations, resulting in lower co-infection rates.…”
Section: Discussioncontrasting
confidence: 57%
“…25 HIV-HCV co-infection was low (ranging from 30.7% to 33.3% among persons with HIV across reference methods) in this sample as compared with other PWID studies (80-89%). 7,21,22 Some of this may be attributable to age as anti-HCV is less prevalent among younger populations, resulting in lower co-infection rates.…”
Section: Discussioncontrasting
confidence: 57%
“…In brief, we calibrated model outputs to historic HIV surveillance data from the New York City Department of Health & Mental Hygiene, 35,36 and to previously validated estimates of key epidemiologic outcomes for PWID, computed for the New York MSA between 1992 and 2002. 18,37,38 We also used historical HIV incidence estimates (1992-2002) for New York PWID to calibrate the primary outcome of interest (see Exhibit 2). 3 Calibrated outputs for other variables of interest (e.g., drug user prevalence, AIDS incidence) are shown Appendix exhibits A7-A9.…”
Section: Methodsmentioning
confidence: 99%
“…And, P11=P44, P12=P42, P13=P43, P17=P27=P37=P47= P57=P67=μ and for k=1,…, (27, Some research has found that following spontaneous clearance of an acute infection a proportion of individuals may have protective immunity to re-infection; however, findings regarding a conferring of a protective immunity are equivocal [40][41][42][43]. In order to capture the possibility of some level of a protective immunity, a corresponding state (z) was included in the natural history model with a low transition probability (0.25) [19].…”
Section: Quasi-markov Model Transition Probabilities and Parametersmentioning
confidence: 99%